2007
DOI: 10.1037/0012-1649.43.1.159
|View full text |Cite
|
Sign up to set email alerts
|

The role of domain-specific practice, handedness, and starting age in chess.

Abstract: The respective roles of the environment and innate talent have been a recurrent question for research into expertise. The authors investigated markers of talent, environment, and critical period for the acquisition of expert performance in chess. Argentinian chess players (N = 104), ranging from weak amateurs to grandmasters, completed a questionnaire measuring variables including individual and group practice, starting age, and handedness. The study reaffirms the importance of practice for reaching high level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
120
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 74 publications
5
120
0
6
Order By: Relevance
“…As some studies have indicated, practice is not the only sufficient condition for reaching high levels of expertise. In Gobet and Campitelli's (2007) study of chess players, a strong correlation was found between chess skill and number of hours of practice. However, the high variability in the number of hours of deliberate practice of between 3,000 and 24,000 hours is an indication that other factors may be responsible for the acquisition of expertise in chess.…”
Section: Development Of Expertisementioning
confidence: 99%
“…As some studies have indicated, practice is not the only sufficient condition for reaching high levels of expertise. In Gobet and Campitelli's (2007) study of chess players, a strong correlation was found between chess skill and number of hours of practice. However, the high variability in the number of hours of deliberate practice of between 3,000 and 24,000 hours is an indication that other factors may be responsible for the acquisition of expertise in chess.…”
Section: Development Of Expertisementioning
confidence: 99%
“…First, while deliberate practice does have a critical role to play in some areas of expertise, notably chess and music, it is not the sole determinant of success that popular treatises (Gladwell 2008) promise. There is in fact enormous variation in time to master even in well studied areas like chess (Gobet and Campitelli 2003). And while some studies have indicated that general aptitude is not a significant predictor of performance, other studies contradict this.…”
mentioning
confidence: 71%
“…For example, a range from 3 016hr to 23 608hr (SD 5 538hr) in total practice accumulated, was verified for chess (Gobet & Campitelli, 2007). Furthermore, variability concerning practice time could additionally be identified in other sports.…”
Section: Participantsmentioning
confidence: 80%
“…When considering years of experience, previous research has suggested that expertise is attained over a period of ten years of practice (Ericsson, et al, 1993) or 10 000 hr (Ericsson, Prietula, & Cokely, 2007); however, studies in chess have shown that the attainment of expertise, concerning the number of hours of practice, may significantly vary (Gobet & Campitelli, 2007). For example, a range from 3 016hr to 23 608hr (SD 5 538hr) in total practice accumulated, was verified for chess (Gobet & Campitelli, 2007).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation